Qualitative and quantitative evidence of anti-glutamic acid decarboxylase-specific intrathecal antibody synthesis in patients with stiff person syndrome - Jarius, Sven; Stich, O.; Speck, J.; Rasiah, Ch.; Wildemann, Brigitte; Meinck, Hans-Michael; Rauer, S. (Journal of neuroimmunology, 2010)
Background - The stiff person syndrome (SPS) is a CNS disorder of putative autoimmune aetiology, which is clinically characterized by severe rigidity and spasms. In most cases, SPS is associated with serum antibodies against glutamic acid decarboxylase (GAD-Ab). Recent studies suggested that GAD-Ab might be directly involved in the pathogenesis of SPS. Further support for this hypothesis would come from studies providing qualitative evidence for the presence of GAD-Ab-producing B cell clones within the CNS of patients with SPS. - Objective and methods - To address that issue, we (i) analysed paired cerebrospinal fluid (CSF) and serum samples from ten GAD-Ab positive patients with SPS and controls by an antigen-driven affinity blotting technique for the presence of GAD-specific oligoclonal IgG bands (OCBs) in the CSF, and (ii) examined the immunoreactive pattern of CSF and serum IgG to recombinant GAD by immunoblotting. To confirm our results quantitatively, we (iii) assessed anti-GAD antibody reactivity in CSF and serum using ELISA and evaluated the GAD-specific antibody index. - Results - GAD-specific oligoclonal bands exclusively or predominately in CSF compared to the corresponding serum were detected in 10/10 patients with GAD-positive SPS but in none of the controls. Immunoblotting revealed stronger staining in the CSF, suggestive of intrathecal IgG synthesis, in 7/10 patients upon visual inspection, and in 8/10 patients upon densitometric analysis. A positive GAD-specific antibody index was found in 9/10 patients. - Conclusions - Here we demonstrate for the first time that IgG OCBs in SPS bind GAD. Our findings contribute to the ongoing discussion on whether the autoimmune process against GAD is involved in the pathogenesis of SPS by indicating that anti-GAD-Ab is produced by B cell clones within the CNS.